Renewed Minds and Redeemed Inheritance: Pauline Eschatology in Eph 4:17–32 - James Andrew Kingsley (Religions)
This article examines the eschatology in Eph 4:17–32 and argues that the section represents an understanding of “inaugurated eschatology” that is consistent with the undisputed letters of Paul. In the letter, believers are called to a metaphorical resurrection from the corruption and ignorance of the old self (2:1–3; 4:17–22) to a renewed life in the present modeled after the image of God (4:24) and guided by the truth in Jesus (4:21). With minds renewed as such, readers of Ephesians may “discern what is pleasing to the Lord” (5:10) as they “understand what the will of the Lord is” (5:17) in everyday decisions of character and conduct (e.g., 4:25–6:9). The “already” resurrection and renewed mind yet await the “not yet” resurrection of the final day. Indeed, the renewal of the mind anticipates further and final renewal of the whole person (i.e., mind and body) on the future “day of redemption” (4:30)—the day in which the present rising will be made complete as the physical body rises to die no more (cf. 1 Thess 5:2; 4:2; 2 Thess 1:10; 2:2–3; 2 Tim 1:12, 18; 4:8).